Functional analysis of extracellular polymeric substances (EPS) during the granulation of aerobic sludge: Relationship among EPS, granulation and nutrients removal - Liu, Xiaoying; Pei, Qianqian; Han, Hongyu; Yin, Hui; Chen, Ming; Guo, Chao; Li, Junli; Qiu, Huan (Environmental research, 2022)
Extracellular polymeric substances (EPS) with high molecular weights, secreted from microorganisms, play a critical functional role in the aerobic granular sludge (AGS). To investigate the level and function of EPS during the granulation of aerobic sludge and in the mature AGS, a sequencing batch reactor (SBR) was operated for 70 days. Aerobic granules with an average diameter of 0.25 mm were obtained with reducing settling time of sludge. Simultaneous removals of COD, nitrogen and phosphorus by the mature AGS exceeded 90, 95 and 95%, respectively. The EPS content increased significantly to above 333 mg/g MLVSS during the initial stage, and after that, it stabilized at about 240 mg/g MLVSS as the mature AGS formed, higher than that of the seed sludge (212 mg/g MLVSS). The increased EPS contents showed a negative correlation with SVI values, while a strong positive relationship with the formation of the AGS. The protein/polysaccharide (PN/PS) ratio in the EPS increased from 1.42 to 4.17, and TP/MLSS increased to about 6%, with the formation of AGS. The proportion of extracellular-P increased with the increase of EPS, and then maintained stable at about 20%, indicating EPS promoted the removal of phosphorus. Furthermore, the results from the Standards, Measurements and Testing (SMT) and X-Ray Diffraction (XRD) showed that phosphorus in the AGS mainly existed in the form of inorganic phosphorus (IP) and the proportion of Ca5(PO4)3(OH) in IP was up to 92%. This investigation demonstrated that EPS had a positive relationship with the sludge granulation and nutrients removal. •Increased EPS content is conducive to aerobic sludge granulation formation.•Protein is the predominant composition in EPS contributed to sludge granulation.•The increased EPS promote the phosphorus removal of AGS.•Phosphorus in the AGS mainly exists in the form of inorganic phosphorus.